Other-Regarding Preferences and Performance Pay : An Experiment on Incentives and Sorting - Marie-Claire Villeval; Tor Eriksson (Institute for the Study of Labor (IZA), 2004)
Variable pay not only creates a link between pay and performance but may also help firms in attracting the more productive employees (Lazear 1986, 2000). However, due to lack of natural data, empirical analyses of the relative importance of the selection and incentive effects of pay schemes are so far thin on the ground. In addition, these effects may be influenced by the nature of the relationship between the firm and its employees. This paper reports results of a laboratory experiment that analyzes the influence of other-regarding preferences on sorting and incentives. Experimental evidence shows that (i) the opportunity to switch to piece-rate increases the average level of output and its variance; (ii) there is a concentration of high skill workers in performance pay firms; (iii) however, in repeated interactions, efficiency wages coupled with reciprocity and inequality aversion reduce the attraction of performance related pay. Other-regarding preferences influence both the provision of incentives and their sorting effect.
Keywords: M52; J33; J31; C81; C91; 330; performance pay; incentives; sorting; selection; other-regarding preferences; experiment; Leistungsorientierte Vergütung; Leistungsanreiz; Personalauswahl; Gerechtigkeit; Experiment; reciprocity